40th anniversary of studies in symbolic interaction - Denzin, Norman K. (Studies in symbolic interaction, 2013)
To mark 40 volumes of Studies in symbolic interaction, this volume includes a special introduction from series editor, Norman K. Denzin. This 40th volume advances critical discourse on several fronts at the same time, including a report from the First contemporary ethnography across the disciplines hui, Waikato, New Zealand; New empirical studies by D. Coates, J. Johnson, D. Altheide, C. J. Schneider and D. Trotter, R. J. Berger, C. Corroto, J. Flad, and R. Quinney, and B. Jarrett (respectively): new religious movements, the California school of symbolic interaction, Terrorism and the national security university, the 2011 Vancouver Riot, The Terrains of Medical Diagnosis and Treatment, and mediation processes. In a separate section to highlight the diverse and challenging aspects of symbolic interactionism; Ryan Turner asks if animals have selves? Michael Katovich and Robert Young and Carol Thompson use Turners article as a springboard for insightful commentary on the selves of other animals and the selves of humans.